Exploring The Meaning Of Islamic Accounting Courses For Students: A Phenomenological Approach - Husain, Fauziah; Aisyah, Mitra Riani; Musa, Nurain (JAS (Jurnal Akuntansi Syariah), 2024)
This research aims to explore the meaning of Islamic accounting courses for students. This qualitative research uses an interpretive paradigm and a transcendental phenomenological approach. The data source uses primary data with observation and interview data collection techniques, where the research informants are 20 students who have programmed Islamic accounting courses in the Islamic accounting study program at IAIN Sultan Amai Gorontalo. Before data analysis is carried out, a data validity test consists of credibility, dependability and confirmability tests. This research shows that learning Islamic accounting courses must focus on developing student competencies, optimizing business processes, and developing Islamic accounting applications. This research can contribute to developing academic literature on Islamic accounting by expanding understanding of the effectiveness of learning models on students' understanding of Islamic accounting courses. This research can contribute to universities improving and enhancing Islamic accounting learning models, making them more relevant and valuable for students in the world of work.